Regulatory objectives vs fiscal interests: Are German casino locations motivated by beggar-thy-neighbor policy? An empirical analysis - Justus Haucap; Radivoje Nedic; Talha Şimşek (European Journal of Law and Economics, 2022)
In this paper we provide an empirical analysis of German casino locations. Due to the "mercantilistic background" of casinos, we assume that casinos are more likely to be found at borders and in tourist areas. Even though~location decisions have been made in the past, we use cross-sectional data at county level to analyze whether the current locations of casinos are consistent with present-day policy objectives. We discuss whether fiscal incentives and/or regulatory objectives to prevent harmful gambling are relevant for today's locations of German casinos. For our empirical analysis we use location and tourism indicators which are both significant factors for the location of German casinos. We find that the likelihood of a casino location increases if a county is located at a state border. We conjecture~that border locations are chosen to share negative externalities of gambling with neighboring states while attracting revenues from out-of-state gamblers. This can be viewed as a type of beggar-thy-neighbor policy, which~is inconsistent, however, with the objectives of the State Treaty, which is to provide legal gambling opportunities for the population within the state. For better implementation of the objectives, a more balanced distribution of casinos throughout the urbanized regions in Germany is recommended.
Keywords: D72; L83; L88; H7; 340; Casinos locations; Negative externalities; Gambling regulation; State border effect; Logit model; Urbanization